Inclusive governance and policies for gender equality and climate resilience - Kosec, Katrina (CGIAR GENDER Impact Platform, 2023)
Katrina Kosec, lead of the work package VOICE, echos the need to shift the narrative of women's empowerment to focus on women’s power. She highlights that the goal of VOICE is to amplify women's voice and agency in the policy environment and governance of agri-food systems and to empower stakeholders with evidence-based strategies for doing so. Discussant Kuntalika Kumbhakar, Integrator at Professional Assistance for Development Action (PRADAN), shares her experience with working on gender equality, climate change, and inclusive governance, emphasizing the importance of placing women at the center of interventions, giving them trainings in advanced agricultural technologies and practices.